Cruise tourism: factors influencing the intention to return to Lisbon destination - Figueira, Lisandra Josefa Abreu (2018)
According to CNN, Lisbon might be the “coolest city in Europe”. Lisbon has been considered a very popular tourism destination and it is possible to see this through the number of tourists that are visiting the Portuguese capital. This “boom” also occurred in cruise tourism with the distinction of Lisbon as “Europe’s Leading Cruise Destination” by the World Travel Awards. Subsequently, understanding which are the factors that tourists appreciate the most and what can bring them back to Lisbon have been gaining a lot of importance. Previous studies incorporating destination image and cruise tourism did not explore pride and prestige as possible antecedents of revisiting a destination or did not find significant conclusions when it comes to the relationship between destination image and intention to return. This research examines the complex relationship between the components of image formation process and destination image as well as analyses the influence of destination image and other possible antecedents in tourist’s behavioural intentions, having into account the moderator effect of economic status. The findings verified the existence of a significant relationship between overall destination image and intention to return and recognized the critical role of conative image in the overall destination image of Lisbon. Moreover, it was possible to conclude that prestige of the cruise acts as an antecedent of intention to return. Practically, this dissertation highlights the important role of conative image and overall destination image and introduces prestige of the cruise as a key factor in intention to return to a destination.